Examination of relationship between simple analysis data of rugby and victory / defeat - focusing on Super Rugby 2018 - Shimozono, H.; Murakami, J.; Sasaki, K.; Watanabe, I. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: This research was to investigate the relationship between official data of Super Rugby in 2018 season and victory / defeat. In recent research on rugby, we examined characteristics of the game, the degree of fatigue during game using GPS. In this research, we Investigated the cause related to victory or defeat. Methods: In this study, we analysed 127 matches of the 2018 season`s Super Rugby. Analysis items were qualitative analyses on attack, defence, kick, set play, and the number of foul play. For the analysis method, use official data of Super Rugby. (https://sanzarrugby.com/superrugby/) Results: It is currently being analysed, but the following can be suggested. 1) Success or failure of set play is related to victory or defeat 2) It seems that defence is more Involved than defence against victory or defeat 3) The penalty number is related to the score 4) It Is possible to extract data related to victory or defeat from official data Conclusion: Super rugby is currently in the season, but results are given at the time In presentation. According to the current results of analysis, the success of set play, the success of defence, and the small number of offenses were Important In the winning team of Super Rugby. It is likely that clarifying the items related to victory and defeat and the characteristics of the team advanced to the finals tournament will be revealed.